1998
DOI: 10.1002/(sici)1097-4547(19981101)54:3<382::aid-jnr9>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects hippocampal neurons in vivo against kainic acid-induced damage in mice

Abstract: In this investigation, 40 mg/kg of the excitatory neurotoxin kainic acid (KA) was subcutaneously administered to CD2-F1 mice. In this mouse strain morphological damage induced by KA in the hippocampus was markedly concentrated in the CA3 pyramidal neurons. Neuronal injury was accompanied by several pathological neurobehavioral activities including arching of tail, tremors and seizures, and by certain biochemical changes, i.e., increased lipid peroxidation products (LPO) in the brain. When melatonin was injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 55 publications
1
55
1
1
Order By: Relevance
“…Both experimental and clinical anticonvulsant activity of melatonin was reported [Molina-Carballo et al, 1997;Lapin et al, 1998]. Reduced melatonin levels are related to increased brain damage after stroke or excitotoxic seizures in rats [Manev et al, 1996], whereas melatonin protected the brain against kainic acid or quinolinic acid oxidative damage Tan et al, 1998;Cabrera et al, 2000]. Electrophysiological experiments further demonstrated the antagonism of melatonin against the NMDA-induced excitotoxicity, an effect involving the inhibition of the nNOS [Escames et al, 1996;Leó n et al, 1998Leó n et al, , 2000.…”
Section: Melatonin and Ros And Rnsmentioning
confidence: 99%
“…Both experimental and clinical anticonvulsant activity of melatonin was reported [Molina-Carballo et al, 1997;Lapin et al, 1998]. Reduced melatonin levels are related to increased brain damage after stroke or excitotoxic seizures in rats [Manev et al, 1996], whereas melatonin protected the brain against kainic acid or quinolinic acid oxidative damage Tan et al, 1998;Cabrera et al, 2000]. Electrophysiological experiments further demonstrated the antagonism of melatonin against the NMDA-induced excitotoxicity, an effect involving the inhibition of the nNOS [Escames et al, 1996;Leó n et al, 1998Leó n et al, , 2000.…”
Section: Melatonin and Ros And Rnsmentioning
confidence: 99%
“…In this study the authors documented that melatonin did not directly inhibit the action of kainic acid on lymphoctes but had an anti-inflammatory and antioxidant mechanism which was evident by the expression mRNA of MAPK 14, iNOS and other inflammatory cytokine levels, However attenuation of free radical species and proinflammatory cytokines was resulted by MLT treatment in a concentration dependent manner. In vivo as well, melatonin reduced the ability of kainic acid to kill neurons in both the cerebellum and in the hippocampus [29,30]. Moreover, melatonin reduced the associated neural lipid peroxidation as well as preventing the death of the majority of the rats that received kainic acid [31].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, single cell suspension of splenic lymphocytes was divided in to several groups; each group contained 1 ml of the splenic lymphocytes single cell suspension in triplicate. The concentration of kainic acid and melatonin were fixed according to the authors earlier studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. First group I was kept as normal control 9 without any treatment); group II was treated with 1 mM of kainic acid alone (KA); group III was treated with 1 mM melatonin alone (MLT); group IV was treated with KA (1 mM)+MLT (0.25 mM) in combination; groups V was treated with KA (1 mM)+MLT (0.5 mM) in combination, groups VI was treated with KA (1 mM)+MLT (1 mM) in combination.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, to interfere with increased ROS during the onset of epilepsy appears to be another possible strategy for therapy. Natural antioxidant compounds such as vitamin C and E, melatonin and catalase have been shown to decrease oxidative stress and alleviate the seizure-induced brain injury (MacGrego et al, 1996;Tan et al, 1998). It has been reported that clinical trial of vitamin E as a therapy for epilepsy is controversial because it failed to improve seizure activity in pediatric patients.…”
Section: Therapeutic Approaches To Target Mitochondrial Bioenergeticsmentioning
confidence: 99%